Raman spectroscopy detects adulterated counter‐ions in pharmaceuticals. (3rd February 2022) - Fuini, Evan; Reimers, Alexandra; Hudspeth, Amber; Kucera, Kaury; Light, David
Abstract: Raman spectroscopy provides accurate and cost‐effective quality control of pharmaceuticals, which is essential for maintaining the confidence of dispensing physicians and patient's adherence to therapeutic regimens. For drug salts that contain a counter‐ion, the active pharmaceutical ingredient and counter‐ion combination is optimized for the intended therapeutic effect. Drug salts with multiple alternative counter‐ions are developed, dosed, and regulated independently and case study one demonstrates how an adulterated medication can contain a different counter‐ion than the label claim. Three additional case studies are performed that showcase how Raman spectroscopy can be applied as a cost‐effective alternative detection technique of both label claim drug and counter‐ion when compared to more commonly used HPLC‐UV methods. Abstract : This study showcases Raman spectroscopy's ability to efficiently identify an adulterated medication sold in the United States. Compared to HPLC‐UV, Raman spectroscopy is an excellent technique for surveillance of drugs and counter ions in medications as demonstrated across four case studies.